Perceptions of the impact of a large-scale collaborative improvement programme: experience in the UK Safer Patients Initiative. - Benn, J; Burnett, S; Parand, A; Pinto, A; Iskander, S; Vincent, C (2009)
RATIONALE AND AIMS: In several countries, collaborative improvement programmes involving multiple health care organizations have been developed to address the issue of patient safety and reliability of care at an organization-wide level. In the UK, the Health Foundation's Safer Patients Initiative (SPI) was developed to achieve breakthrough improvement in the quality and safety of care in 24 acute hospital Trusts between 2004 and 2008. Research evidence for the effectiveness of programmes of this type and the mechanisms by which positive outcomes are achieved remains limited. We report a multi-method preliminary study based upon phase 1 of SPI to understand participant's perceptions of the local impact of the programme and to form the basis of future research in this area. METHODS: Data were collected on the perceived local impact of SPI on a range of clinical, organizational and social dimensions relating to care quality and safety. Data were collected retrospectively from local SPI programme improvement teams using semi-structured interviews and surveys. Qualitative and quantitative analyses were performed, and the results synthesized under common themes and frameworks. RESULTS: Specific dimensions of care systems commonly considered to be affected by SPI, included culture, strategic priority, organizational capability and clinical care delivery. Survey data revealed the perceived importance for success of a range of programme components: quality improvement methodology, learning sessions and programme faculty support, along with predefined clinical practice changes. Safety climate and capability dimensions rated as most sensitive to the effects of the SPI programme related to multi-professional engagement and communication, the degree of routine monitoring of care processes and the capacity to evaluate the impact of changes to clinical work systems. CONCLUSIONS: Study findings support the view that programmes such as SPI have considerable impact upon the cultural, inter-professional, strategic and organizational aspects of care delivery, in addition to clinical working practices. The specific implications for understanding the effects of complex organization-level interventions and future research design are discussed.